Social Comparison on Social Media Increases Career Frustration: A Focus on the Mitigating Effect of Companionship - Fukubayashi, Nao; Fuji, Kei (Frontiers in Psychology, 2021)
Social media has become a platform for the daily exchange of information. Although some studies have explored the role and influence of social media on career development, few have examined how daily social media use impacts individuals’ perceptions and emotions regarding their careers. This study aimed to examine this point through two surveys. We predicted that social comparison would mediate the link between social media usage and its psychological impact. Moreover, we proposed that the impact would be mitigated by social interactions (companionship). Study 1 (a self-reported survey that included 309 Japanese employees) demonstrated that viewing other users’ positive posts about their careers could lead to career frustration through social comparison. Concurrently, this study revealed that daily casual interaction with others reduced career frustration. Study 2 was based on an analysis of 1,254 responses obtained from a 7-day experience sampling method survey. It found that viewing other people’s career-related posts was associated with upward, downward, and non-directional social comparison. In turn, upward social comparison evoked career frustration on both between- and within-person levels, while downward comparison decreased career frustration on a between-person level. Similar to Study 1, Study 2’s results indicated that career frustration was mitigated by casual communication with others. Both studies provide evidence that: 1) daily social media use affects one’s perception and feelings around their career through social comparison, and 2) career frustration evoked through virtual interactions with others is mitigated by casual interactions in a face-to-face setting. Implications are discussed.